FLOOD MANAGEMENT SYSTEM USING A SOUND SENSOR ARDUINO BASED - Nazwan Putera Prayuda; Aditya Putra Firmansyah, Rafly Septia Sandy, Paduloh (Adisam Publisher, 2024)
Natural disasters are events that arise due to careless human actions. Natural disasters such as floods cause a lot of material or psychological losses. Floods often cause people to lose their homes, livelihoods, and even cause trauma due to the loss of family members. So we must prevent floods from occurring in order to achieve a safe and peaceful life. In this research, a Sound Sensor was used as a detection tool combined with the Arduino Water Level System so that the movement of water flow can be seen, especially in areas that are prone to flooding. The results of this research showed that there was a low scale with a small sound on the red light, then there was a medium scale with a medium sound on the green light, and also a high scale with a large sound on the blue light.